Extraction of Frozen Berry Raw Materials with a Vibration Tray Device - Liubov V. Plotnikova; Igor B. Plotnikov; Pavel P. Ivanov; Andrey G. Semenov; Irina O. Plotnikova; Konstantin B. Plotnikov (Техника и технология пищевых производств)
Introduction. Products containing natural extracts are in great demand. However, poor production technologies make them too expensive to satisfy consumer demand. As a result, a variety of intensification methods have been developed to increase the economic efficiency of extraction, e.g. low-frequency mechanical vibrations. However, frozen raw materials have to be processed at low temperatures, which makes the method less efficient. The research objective was to intensify the extraction process from frozen berries in a vibration tray device by increasing the temperature of the system of interacting phases. Study objects and methods. The research involved frozen cranberries and blueberries. They grow everywhere in Western Siberia and are rich vitamins and minerals. The berries were subjected to slow freezing at –18°C, which destroyed the cell structure and increased the processing efficiency. The study was carried out in a lab device with a vibrating tray. All parameters were measured by standard methods. Results and discussion. The extraction device was equipped with a jacket into which a coolant was fed, i.e. water with a temperature of 55°C. A preliminary series of experiments revealed two negative aspects associated with the supply of coolant into the jacket. First, the surface layer started to thaw, which reduced the efficiency of grinding. Second, the processing time increased. A new method was developed to solve these problems: the coolant was supplied at the end of the grinding. The time of the coolant supply depended on the type of raw materials. The processes that occurred within the device depended on two factors: the frequency of vibrations of the tray and the diameter of the holes in the tray. These factors could be adjusted to intensify the process, but they increased the power costs and energy consumption. A series of experiments determined the optimal values of these parameters. A mathematical analysis revealed regression equations, i.e. how the destruction time and power costs affected the main parameters. The established optimal process parameters made it possible to determine the minimal time of the destruction process: for cranberries – 2.5 min, for blueberries – 1.5 min. The minimal power consumption was 17.8 watts for cranberries and 11.7 watts for blueberries. Conclusion. The research increased the economic efficiency of the technological process of natural extraction, which can reduce the cost of the finished product and increase its availability. The values of the process parameters can be used to design new similar devices and serve as practical recommendations for berry extraction in vibration tray devices.